2017
DOI: 10.25135/rnp.07.17.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Guided Isolation of Active Compounds from Alchemilla barbatiflora Juz.

Abstract: Abstract:The aerial parts of Alchemilla L. species (Rosaceae) are used internally as diuretic, laxative, tonic and externally for wound healing in Turkish folk medicine. Antioxidant effects of the extracts, fractions and isolated compounds from the aerial parts of A. barbatiflora Juz. were investigated with following methods: 1,1-diphenyl-2-picryl-hydrazyl (DPPH), and superoxide radical scavenging (SOD), phosphomolibdenum-reducing antioxidant power (PRAP), ferric-reducing antioxidant power (FRAP) assays. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…153 Kaempferol, myricetin, quercetin, isorhamnetin, galangin, morin, and their glycosides are the prevalent naturally occurring avonols, mostly found as O-glycosides. [154][155][156][157][158][159][160] So far, several avonols such as quercetin from Olea europaea, kaempferol from Hypericum laricifolium, and Crocus sativus, quercetin-4 0 -O-beta-D-glucoside from Parornix bifurca, quercetin glucopyranoside and kaempferol glucopyranoside from mulberry leaves, morin and 2,3-cis-dihydromorin, 2,3-transdihydromorin from Chloropsis cochinchinensis, were found to act as tyrosinase inhibitors (Table 12). Moreover, it was reported that three 3-hydroxyavones including kaempferol, galangin, and quercetin inhibit the L-DOPA oxidation process catalyzed by tyrosinase, and apparently, this TI activity arises from their Cu 2+ chelating ability.…”
Section: Flavonolsmentioning
confidence: 99%
“…153 Kaempferol, myricetin, quercetin, isorhamnetin, galangin, morin, and their glycosides are the prevalent naturally occurring avonols, mostly found as O-glycosides. [154][155][156][157][158][159][160] So far, several avonols such as quercetin from Olea europaea, kaempferol from Hypericum laricifolium, and Crocus sativus, quercetin-4 0 -O-beta-D-glucoside from Parornix bifurca, quercetin glucopyranoside and kaempferol glucopyranoside from mulberry leaves, morin and 2,3-cis-dihydromorin, 2,3-transdihydromorin from Chloropsis cochinchinensis, were found to act as tyrosinase inhibitors (Table 12). Moreover, it was reported that three 3-hydroxyavones including kaempferol, galangin, and quercetin inhibit the L-DOPA oxidation process catalyzed by tyrosinase, and apparently, this TI activity arises from their Cu 2+ chelating ability.…”
Section: Flavonolsmentioning
confidence: 99%
“…A significant melanogenesis inhibition potential has been reported also for galangin (IC 50 = 3.55 µM) [52], isoliquiritigenin (IC 50 = 4.85 µM) [53], kaempferol (IC 50 = 5.5 µM) [54], and dihydromorin (IC 50 = 9.4 µM) [55], belonging to different flavonoid subfamilies, but all characterized by at least one resorcinol moiety. IC50 values in the range 20-150 µM have instead been reported for catechins [56][57][58][59]. Among natural phenolic compounds acting as tyrosinase inhibitors (Supplementary Materials, Table S1), flavonoids are the most representative class.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…The obtained methanol extract (304 g) was suspended in water and successively partitioned to provide the following fractions viz., n-hexane (26 g), CH 2 Cl 2 (11 g), EtOAc (25 g), n-BuOH (26 g) and aqueous (44.5 g). The n-hexane fraction was loaded on silica gel column chromatography (CC) and eluted with n-hexane, followed by increasing concentrations of EtOAc in n-hexane (10,20,30, and 100%) to give four fractions H A-D . Fraction H B (0.5 g) was further purified by CC using nhexane:EtOAc (80:20 to 60:40) to provide lyciumate (1, 5 mg) [2], dehydrocostus lactone (2, 60 mg) and costunolide (3, 45 mg) [3], while fraction H A (0.3 g) on further CC purification with nhexane:EtOAc (90:10) as eluent provided nonacosane-10-ol (12, 12 mg) [4].…”
Section: Present Studymentioning
confidence: 99%
“…On the other hand the occurrence of catechin (4) in the title plant is in agreement with similar types of compounds previously reported from other Lycium species i.e from L. chinens [17]. Importantly, compound 4 is now reported for the first time as being isolated from the genus Lycium while it has previously been reported to be present in various plants of Solanaceae viz., potato (Solanum tuberosum) [18], Amanaga capsicum, Lycopersicon esculentum Mill, Capsicum annuum [19], and Alchemilla barbatiflora Juz [20]. The diester lyciumaside (5) has previously been reported from the title plant [2].…”
Section: Chemotaxonomic Significancementioning
confidence: 99%